Kalam-o-Nizaam - Syed Ammar Bukhari (KARACHI Syed Ammar Bukhari)
The book is part poetry part descriptive. Most of the topics are co relating the Islam and Socio-Political system of society.
The book is part poetry part descriptive. Most of the topics are co relating the Islam and Socio-Political system of society.